IMPLEMENTASI TAKSONOMI BLOOM DALAM EVALUASI PEMBELAJARAN - Ikmal Nur Afnan; Noor Rizal Yusuf; Yusuf zaky Fachruddin; Gilang Ramadhan (ADIBA : JOURNAL OF EDUCATION, 2025)
Evaluation is necessary in the education system. In order to find out how well the educational process is running according to set criteria, it is necessary to implement an assessment system. In the context of evaluation, this means a phase of gradually collecting data before analyzing it to draw conclusions about the success of the learning system and whether it has met the proper objectives of national education. Since numerical data was not intended to be part of the results of this study, qualitative methods were used in its design. Given the nature of the topic under study, qualitative techniques were deemed most suitable for the collection and analysis of data for this study. ease of accessing relevant sources of information, and a more in-depth understanding of the research problem at hand without having to conduct direct experiments are benefits of the literature review approach. Bloom's Taxonomy provides a structured hierarchy for naming abilities in ascending order. There is a relationship for each level of Bloom's Taxonomy. To unlock the top level, you must first master the lower levels. There are three basic parts of Bloom's Taxonomy. cognitive domain, aflective domain, and psychomotor domain. the implementation of Bloom's Taxonomy in learning evaluation, highlights the importance of evaluation to achieve national education goals. Bloom's taxonomy divides educational objectives into three domains: cognitive, aflective, and psychomotor. Evaluation of learning outcomes plays an important role in motivating students and identifying factors that influence their success or failure. However, challenges such as teachers' lack of readiness and community support need to be overcome to achieve the goals of Merdeka Curriculum.